Penerapan Chicken Scratch Embroidery Pada Handbag - Bunga Widhya Nur Hasanah; Yulistiana Yulistiana (Corak, 2025)
The fashion industry continues to evolve with innovations in design, production techniques, and materials. One of the embroidery techniques that has regained attention is Chicken Scratch Embroidery, traditionally applied to gingham fabric. This study aims to implement Chicken Scratch Embroidery in handbag design, incorporating aesthetic and functional aspects. The Double Diamond Model was used in the design process, consisting of four stages: Discover, Define, Develop, and Deliver. The research began with exploring embroidery trends, creating a moodboard, and developing handbag prototypes. The selected handbag design integrates geometric embroidery motifs that enhance the classic and elegant appeal of gingham fabric. The results show that Chicken Scratch Embroidery can enrich handbag aesthetics while maintaining ergonomic functionality. This research contributes to the innovation of traditional embroidery techniques in contemporary fashion products.